2021
DOI: 10.1021/acs.langmuir.0c02675
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of a Humanized Monoclonal Antibody onto Thermoresponsive Copolymer-Grafted Sepharose Fast Flow Sorbents

Abstract: The batch adsorption behavior of a humanized monoclonal antibody (hIgG2 mAb) with thermoresponsive polymer (TRP)-modified Sepharose Fast Flow sorbents with different compositions of grafted copolymers is described. At high protein loadings, the adsorption with negatively charged copolymer-modified sorbents exhibited S-shaped isotherms in most cases, indicative of unrestricted multilayer adsorption. The adsorption capacity of the negatively charged copolymer-modified sorbents increased with an increase in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
0
0
Order By: Relevance
“…The temperature and size of side chains in polymers also affect the strength of the adsorption force. Tan et al [108] found that the affinity of the hIgG2 monoclonal antibody (mAb) with the negatively charged copolymermodified surface was higher for adsorptions at 50 • C compared with 20 • C. Because at this higher temperature (50 • C), hydrophobic and electrostatic interactions were enhanced. In addition, the size of the side chains in the copolymer structure also influences the electrostatic interactions between the copolymer-modified surface and protein molecules.…”
Section: Non-covalent Conjugationmentioning
confidence: 99%
“…The temperature and size of side chains in polymers also affect the strength of the adsorption force. Tan et al [108] found that the affinity of the hIgG2 monoclonal antibody (mAb) with the negatively charged copolymermodified surface was higher for adsorptions at 50 • C compared with 20 • C. Because at this higher temperature (50 • C), hydrophobic and electrostatic interactions were enhanced. In addition, the size of the side chains in the copolymer structure also influences the electrostatic interactions between the copolymer-modified surface and protein molecules.…”
Section: Non-covalent Conjugationmentioning
confidence: 99%